Syllabus design in Business English based on the needs of Economics students - Nove Ria, Tiara; Malik, Djamaludin (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
Business English is one branch of English for Specific Purposes. In determining the abilities to be achieved in learning objectives, material selection, and learning methods in this course, the syllabus design must be tailored to the needs of students and it is better to combine with the real work situation. Therefore, a need analysis is essential to use for designing the syllabus However, the recent syllabus did not match students need so that the aim of this study was to conduct need analysis to develop the Business English syllabus design for Economics students. It was based on two situations, learning needs and target situation needs. The subjects were students, lecturer, graduates and employers. The instruments to collect the data in this study were questionnaire and interviews. This study used quantitative and qualitative method. The results showed that students mostly need speaking skills to be emphasized to learn, while mastering vocabularies was the weakness that the students need to improve. Moreover, they tended to have drilling as the learning method. While the most materials of English Business used in workplace was reading instruction related work and documents. Based on the findings of this study, it can be used for designing the new syllabus.